Rigor and reproducibility training for first year medical students in research pathways - Kate L. Lapane; Catherine E. Dube (Wiley, 2021)
Abstract In the Spring of 2020, we launched a rigor and reproducibility curriculum for medical students in research training programs. This required class consisted of eight, 2‐h sessions, which transitioned to remote learning in response to the coronavirus disease 2019 (COVID‐19) epidemic. The class was graded as pass/fail. Flipped classroom techniques, with multiple hands‐on exercises, were developed for first‐year medical students (MD/PhD [n = 9], Clinical and Translational Research Pathway (CTRP) students [n = 9]). Four focus groups (n = 13 students) and individual interviews with the two instructors were conducted in May 2020. From individual interviews with instructors and focus groups with medical students, the course and its components were favorably reviewed. Students thought the course was novel, important, relevant, and practical-and teaching strategies were effective (e.g., short lectures, interactive small group exercises, and projects). Most students expressed concerns about lack of time for course preparation. Sharper focus and streamlining of preparation work may be required. Pre‐ and post‐student self‐assessments of rigor and reproducibility competencies showed average post‐scores ranging from high/moderate to strong understanding (n = 11). We conclude that rigor and reproducibility can be taught to first‐year medical students in research pathways programs in a highly interactive and remote format. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? The rigor and reproducibility crisis calls for robust training of scientists in best practices for enhancing the research rigor. WHAT QUESTION DID THIS STUDY ADDRESS? We evaluated a curriculum to develop physician‐scientists skilled at documenting research workflow from idea generation to publication with reproducibility in mind. WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? Highly interactive exercises, coupled with a hands‐on replication group project provide a pathway for students to gain competencies important to the improvement of rigor and reproducibility in scientific research. Rigor and reproducibility can be taught in a highly interactive format and using a remote format. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? Formal training is needed to raise awareness of the reproducibility crisis and improve the rigor of research conducted. If techniques taught are used, the transparency and reproducibility of clinical and translational science will be improved.